Failed Products Of Micro, Small And Medium Enterprises In West Kotawaringin Central Kalimantan - Muhammad Zainal Arifin; Jelita Jelita; Ainol Muliansyah (UNIVED Press, 2025)
Many Micro, Small and Medium Enterprises (MSMEs) in West Kotawaringin Regency such as crackers and amplang are relatively expensive. Due to the high cost of kerupuk and amplang, these products are only consumed by people with middle to upper income. The product packaging also does not include the expiry date and components of the ingredients used. Based on initial observations of Micro, Small and Medium Enterprises (MSMEs) in West Kotawaringin, some consumers claim to be dissatisfied with Small Micro Enterprises both in terms of service, product design and in terms of marketing. The approach in this research is descriptive qualitative research method. This method is used to observe or detect various facts or phenomena and social symptoms that are natural (nature) through field observations. The results of this study indicate that there are two factors that cause product failure in West Kotawaringin MSME businesses, namely internal and external factors.